The portrayal of the female protagonists in a selection of short stories by Anne Enright and Claire Keegan - Lausegger, Isabella (2013)
Diese Diplomarbeit analysiert die Darstellung der weiblichen Protagonistinnen in ausgewählten Kurzgeschichten der beiden zeitgenössischen irischen Autorinnen Anne Enright und Claire Keegan. Die diskutierten Texte sind "Green", "Here’s to Love", "Until the Girl Died" und "Yesterday’s Weather" von Anne Enright, sowie "Antarctica", "Love in the Tall Grass", "Men and Women" und "Quare Name for a Boy" von Claire Keegan. Diese Auswahl basiert auf den Sammelausgaben "Antarctica" (Keegan 1999) und "Yesterday’s Weather" (Enright 2008). Neben der Untersuchung der Charakterisierungen der Protagonistinnen, welche einen zentralen Aspekt dieser Diplomarbeit darstellt, wird ein Einblick in den relevanten kulturhistorischen Kontext gegeben. Außerdem werden die beiden Autorinnen und ihr literarisches Schaffen, welches häufig mit postmodernen und postfeministischen Theorien in Verbindung gebracht wird, vorgestellt. Überdies wird anhand von erzähltheoretischen Überlegungen untersucht, in welcher Form die weiblichen Figuren in den Texten befähigt werden ihre Stimmen zu nutzen um ihre Geschichten, Gedanken und Gefühle zu vermitteln. In diesem Zusammenhang werden stereotypische Vorstellungen von Weiblichkeit – im irischen Kontext – sowie deren Konstruktion und Dekonstruktion in den Texten diskutiert. Darüber hinaus werden die individuellen Lebenskrisen und Identitätskonstruktionen der weiblichen Protagonistinnen jeweils in Relation zu den anderen Kurzgeschichten gesetzt. Da die Texte Parallelen bezüglich literarischer Themen und Motive aufweisen, stellen auch diese eine wichtige Komponente dieser Diplomarbeit dar. Durch eine vergleichende Analyse konnte unter anderem festgestellt werden, dass die Protagonistinnen der acht Kurzgeschichten starke Frauenfiguren sind, die ihr Schicksal, ihre Geschichten und ihre Beziehungen selbst in die Hand nehmen. This thesis analyses the portrayal of the female protagonists in selected short stories by the two contemporary Irish women writers Anne Enright and Claire Keegan. In particular, not only Enright’s "Green", "Here’s to Love", "Until the Girl Died" and "Yesterday’s Weather", but also Keegan’s "Antarctica", "Love in the Tall Grass", "Men and Women" and "Quare Name for a Boy" are discussed. This selection of texts is based on two short story collections, namely Keegan’s "Antarctica" (1999) and Enright’s "Yesterday’s Weather" (2008). Although all of the main figures have individual stories and specific character traits, certain interesting similarities can be detected: They are strong and open-minded women who make their own decisions and decide to tell their stories. As far as methodology is concerned, basically three theoretical frameworks are applied in this study, namely close-reading, narrative theory and gender theory. To provide the reader with the socio-cultural context of the topic, an overview of the historical background of Irish women and Irish women writers from the late twentieth to the early twenty-first centuries is given. Moreover, the authors Anne Enright and Claire Keegan, who are frequently referred to as postmodern and post-feminist writers, as well as their literary production are introduced. Furthermore, narrative technique with a particular focus on narrative voice is examined and the construction and deconstruction of stereotypical perceptions of Irish womanhood are discussed. Additionally, themes and motifs the short stories have in common are linked to the female protagonists’ lives and sentiments.